Single nucleotide polymorphisms in partial sequences of the gene encoding the large sub-units of ADP-glucose pyrophosphorylase within a representative collection of 10 Musa genotypes - Muhilan Mahendhiran; Jorge Humberto Ramirez-Prado; Rosa Maria Escobedo-Gracia Medrano; Blondy Canto-Canché; Miguel Tzec-Simá; Rosa Grijalva-Arango; Andrew James-Kay (Electronic Journal of Biotechnology, 2014)
Background: ADP-glucose pyrophosphorylase (AGPase) is a rate-limiting enzyme catalyzing the first step in the starch biosynthesis pathway in higher plants. To date, there are no reported variants or isoforms of the AGPase enzyme in bananas (Musa spp. family Musaceae) as is the case of other plants. In this study, genomic DNA sequences homologous to the gene encoding one of the large subunits of the enzyme were amplified from 10 accessions of the genus Musa, including representatives of wild ancestors (AA and BB genomes), dessert bananas (AA, AAA, AB and AAB genomes), plantains (AAB genome) and cooking bananas (ABB and AAA genomes), and studied in order to find single nucleotide polymorphisms (SNP) base variations in Musa accessions. Results: In the 810-base pair amplicons of the AGPase large sub-unit (LSU) gene analyzed in ten Musa accessions, a total of 36 SNPs and insertions/deletions (indels) were found. The phylogenetic analysis revealed fifteen distinct haplotypes, which were grouped into four variants. Deep examination of SNPs in the 2nd exon in the LSU of AGPase showed that at seven locations, five SNPs altered their amino acid sequence. Conclusions: This work reveals the possible number of AGPase enzyme isoforms and their molecular levels in banana. Molecular markers could be designed from SNPs present in these banana accessions. This information could be useful for the development of SNP-based molecular markers for Musa germplasm, and alteration of the allosteric properties of AGPase to increase the starch content and manipulate the starch quality of banana fruits.